2016
DOI: 10.1108/imds-09-2015-0398
|View full text |Cite
|
Sign up to set email alerts
|

Measuring quality perception in electronic commerce

Abstract: Purpose The perceived electronic-service quality (e-SQ) has become a relevant research area, not only in developed but also in smaller, less-developed countries. The purpose of this paper is to provide a description of an analysis into the relationship of the dimensions of perceived e-SQ and satisfaction as well as WOM intention in case of an online bookstore in Hungary where technical development and internet penetration is emerging; however, it is developing from an economic perspective. Beyond this a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Partial least squares (PLS) is used for testing the theoretical framework. PLS is considered suitable when sample size is comparatively small, such as in this study (Kemény et al, 2016; Luo et al, 2015). Second, PLS method does not requires normality of data (Chin, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Partial least squares (PLS) is used for testing the theoretical framework. PLS is considered suitable when sample size is comparatively small, such as in this study (Kemény et al, 2016; Luo et al, 2015). Second, PLS method does not requires normality of data (Chin, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Prospective consumers are increasingly evaluating and appraising different products, services as well as the service performance of online businesses, e-commerce websites or marketplaces before committing themselves to making a purchase (Kemény, Simon, Nagy and Szucs, 2016;Hennig-Thurau, Gwinner, Walsh and Gremler, 2004). Electronic word-of-mouth (e-WOM) communications have often been described as the consumers' positive or negative statements, relating to their knowledge and experience about a product or service provider (Guo, Barnes and Jia, 2017;Rossmann, Ranjan and Sugathan, 2016).…”
Section: E-satisfactionmentioning
confidence: 99%
“…This study showed that the customers were intrigued to share their positive or negative experiences with products and/or services with other online users. Hence, they were willing to cocreate online content for the benefit of prospective consumers (Devereux and Gallarza, 2019;Kemény, 2016;Hennig-Thurau et al, 2004).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…"Efficiency" is defined as "the ability of a customer to get to the web site, find their desired product and information associated with it with minimal effort" (Wang, 2003). Numerous studies found that efficiency has "positive relationship" with customer's satisfaction (Kemény et al, 2016). Similarly, according to Elsharnouby and Mahrous (2015), efficiency majorly affects customer satisfaction and their re-purchase intention.…”
Section: E-sq Attributes E-cs and E-clmentioning
confidence: 99%